2018
DOI: 10.1038/s41598-018-27656-y
|View full text |Cite
|
Sign up to set email alerts
|

The soluble guanylate cyclase stimulator riociguat reduces fibrogenesis and portal pressure in cirrhotic rats

Abstract: In cirrhotic patients, portal hypertension (PHT) deteriorates survival, yet treatment options are limited. A major contributor to increased intrahepatic vasoconstriction in PHT is dysfunctional nitric-oxide signaling. Soluble guanylate cyclase (sGC) is the receptor of nitric-oxide and can be stimulated by riociguat. Riociguat is approved for pulmonary hypertension but has not been studied in liver cirrhosis. In this study we assessed the effects of riociguat on PHT and liver fibrosis in cholestatic (bile duct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 54 publications
(64 reference statements)
2
45
4
Order By: Relevance
“…sGC agonists have shown promising effects in preclinical models of liver fibrosis (Knorr et al 2008;Hall et al 2017). The sGC stimulator riociguat was shown to reduce liver fibrosis and portal pressure in cirrhotic rats (Schwabl et al 2018) and mechanistic studies suggest that sGC modulators may inhibit fibrotic differentiation of hepatic stellate cells (Xiao et al 2015;Hall et al 2017). Nonalcoholic steatohepatitis (NASH) is a liver disease with characteristics of steatosis, inflammation, and fibrosis, and is a growing health concern globally.…”
Section: Liver Diseasesmentioning
confidence: 99%
“…sGC agonists have shown promising effects in preclinical models of liver fibrosis (Knorr et al 2008;Hall et al 2017). The sGC stimulator riociguat was shown to reduce liver fibrosis and portal pressure in cirrhotic rats (Schwabl et al 2018) and mechanistic studies suggest that sGC modulators may inhibit fibrotic differentiation of hepatic stellate cells (Xiao et al 2015;Hall et al 2017). Nonalcoholic steatohepatitis (NASH) is a liver disease with characteristics of steatosis, inflammation, and fibrosis, and is a growing health concern globally.…”
Section: Liver Diseasesmentioning
confidence: 99%
“…Recently, we and others have demonstrated that modulation of cyclic guanosine-3′,5′-monophosphate (cGMP) exerts antiinflammatory and antifibrogenic effects in models of NASH and reduces portal pressure and fibrogenesis in cirrhotic rats (3)(4)(5). In these studies, small molecules with the ability to stimulate soluble guanylate cyclase (sGC), an enzyme that catalyzes the conversion of guanosine triphosphate (GTP) to cGMP, proved to be efficacious in the prevention as well as in the treatment of hepatic inflammation and fibrosis (3)(4)(5). In particular, using an optimized experimental model of NASH induced by a cholinedeficient L-amino acid-defined high-fat diet (CDAHFD) (6), we recently demonstrated that administration of the sGC stimulator praliciguat (PRL) delayed, in a dose-dependent manner, the development of liver inflammation and fibrosis (3).…”
mentioning
confidence: 99%
“…91 Primary cell isolation experiments revealed sGC expression in hepatocytes and HSCs and to a lower extent also in LSECs and KCs. 92 Activation of the sGC by NO results in the production of cyclic guanosine monophosphate (cGMP) and vasodilation. In oxidative stress conditions, as often present in liver diseases, NO signaling and affinity of NO to sGC is disturbed, which contributes to sinusoidal endothelial dysfunction and intrahepatic vasoconstriction.…”
Section: Soluble Guanylyl Cyclasementioning
confidence: 99%
“…105,106 Data obtained from two rat models of PHT (biliary and toxic liver cirrhosis), suggest promising effects of riociguat (sGC stimulator) on the reduction of PP and liver fibrosis. 92 Riociguat decrease hepatic necroinflammation and sinusoidal vascular remodeling, especially in cholestatic cirrhosis. 92 Of note, the safety of riociguat was already investigated and confirmed in patients with up to Child-Pugh B cirrhosis.…”
Section: Sgc Modulation In Liver Fibrosis and Portal Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation